Complexation Behaviour of Glutathione with Metal Ions - K. Singh, Bibhesh (Asian Journal of Chemistry, 2016)
Metal complexes of glutathione (GSH) serve important functions in our biological system and play a dominant role in protein metabolism. They are important constituents of enzymes, proteins and present in many parts of the biological system. Glutathione (GSH, g-glutamate-cystein-glycine) is the most common cellular non-protein thiol in the cell; it exists predominantly in the reduced form (GSH) at concentration 0.1-10 mm and is readily oxidized to the disulphide (GSSG). Because of the presence of potential binding sites in glutathione (reduced), its coordination chemistry is complicated. The present review discusses the interaction of glutathione with various transition and non-transition elements at the molecular level and their biological significance.